AUV homing and docking for remote operations. (15th April 2018) - Palomeras, N.; Vallicrosa, G.; Mallios, A.; Bosch, J.; Vidal, E.; Hurtos, N.; Carreras, M.; Ridao, P.
Abstract: One of the major goals of the SUNRISE FP7 project is to make the Underwater Internet of Things a reality. In this context, the LOON-DOCK project presented here extends the existing Litoral Ocean Observatory Network testbed with a Docking Station tailored to the Sparus II AUV. The docking system allows a remote user to program survey-like missions through a web-based interface as well as to retrieve the data gathered by the AUV once a mission finalizes. To enable the autonomous docking of the AUV, two complementary and cost-effective localization systems have been developed. The first one implements a range-only localization algorithm to approach the docking station while the second, based on active light beacons, provides high accuracy at short ranges to complete the docking maneuver. The system has been extensively tested, in different trials from a controlled water tank environment to more realistic sea operation conditions proving its viability despite very poor water visibility conditions.